Morphological characterization and genetic diversity in lentil (Lens culinaris medikus ssp. Culinaris) germplasm (International Journal of Agricultural Research, Innovation and Technology, 2014)
Genetic divergence of 110 lentil germplasm with checks was assessed based on morphological traits using multivariate analysis. Mahalanobis generalized distance (D2) analysis was used to group the lentil genotypes. Significant variations among lentil genotypes were observed in respect of days to 1st flowering, days to 50% flowering, days to maturity, plant height, and number of pods per peduncle, number of pods per plant, number of seeds per plant, 100 seed weight and yield per plant. Considering the mean values, the germplasm were grouped into ten clusters. The highest number of genotypes (17) was in cluster X and lowest (5) both in cluster II and IV. Cluster IV had the highest cluster mean for number of pods per plant (297.08), number of seeds per plant (594.16), 100 seed weight (1.44 g) and yield per plant (8.53 g). Among them, the highest inter-cluster distance was obtained between the cluster IV and I (24.61) followed by IV and III (22.33), while the lowest was between IX and II (1.63). The maximum value of inter-cluster distance indicated that genotypes belonging to cluster IV were far diverged from those of cluster I. The first female flower initiation was earlier in BD-3812 (49 days) in cluster I and cluster IV had highest grain yield per plant (8.53). BD-3807 produced significant maximum number of pods per plant (298.40) in cluster IV. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21095 Int. J. Agril. Res. Innov. & Tech. 4 (1): 70-76, June, 2014